How are decisions made to access a planned epidural in labour? Midwife-woman interactions in antenatal consultations. (March 2020) - Cole, Lindsay; Turnbull, Deborah; Dahlen, Hannah
Abstract: Objective: The purpose of this study was to examine the ways in the decision to access a planned epidural in labour was topicalised and negotiated between pregnant women and midwives. Design: This article uses conversation analysis to examine how decision-making unfolds in antenatal consultations in a large metropolitan hospital in South Australia. Data were sampled from naturally-occurring interactions between women and midwives in routine antenatal consultations. Analysis focused on talk about planning to access (or, avoid) an epidural during an upcoming labour. Findings: This paper illustrates that in the context of woman-centred care, women are held unilaterally responsible for the decision to accept or reject a planned epidural in labour with little or no input from the midwife. Midwives take a step back from involvement in the discussion beyond the solicitation of a decision from the woman. Women wanting a planned epidural took a strong, assertive stance in the interaction and drew on their previous birthing experience, limiting opportunity for the midwife to engage in meaningful discussion about the risks and benefits. On the other hand, women rejecting a planned epidural were less assertive and engaged in more complex interactional work to account for their decision. Key conclusions: The lack of involvement by midwives may be linked to the non-directive ethos that prevails in maternity care. It is argued that, in this dataset, the institutional imperative for women to know and decide on pain relief while pregnant in order to allocate to a model of care is prioritised over women's aspirations and expectations of childbirth. Implications for practice: By analysing the ways in which midwives and women interact at the point in time at which decisions were made to plan access to an epidural we can continue to reveal underlying forces that drive the rising rates of medical interventions in childbirth. This paper also contributes to research evidence on how midwives manage the potentially contradictory dialect between supporting women's childbirth preferences while also managing institutional requirements and evidence-based practice.